An Analysis of Reality Construction Through Conflicts in Gillian Flynn’s Gone Girl - Monica Prilly Aditya (Passage, 2016)
The complexity of Gone Girl evoked wide aspects to explore. The current study focused on the issue of reality construction in the novel. It was aimed at answering the question of how the male and female central characters constructed the versions of reality through conflicts which were a result of multiple narrative perspectives used in the novel. The data were analyzed by using Bartley, Blanton, and Gilliard’s (2005) three aspects of marital relationship. The findings indicated that the reality in the novel was dominantly constructed through the conflictive marital relationship between the male and female central characters. The conflicts were found in the aspects of marital relationship particularly in the decision making process and the attitude towards gender roles and stereotypes. In terms of decision making, the conflicts resulted from the process and the outcomes of major decision-making including the decision to move to a new city, decision to have children, decision regarding career choices and the decision of getting a divorce. Meanwhile, from the aspect of attitude towards gender roles and stereotypes, the male and female central characters appeared to demonstrate double standards and hypocritical attitudes which led to conflicts in the novel. Therefore, from the findings it could be concluded that the text indicated a tendency for men and women to be involved in conflicts since they had different presumptions, interests, and egos in constructing their version of reality.Key words: reality construction, marital relationship, marital conflicts, decision-making, gender role attitudes, double standardKeywords: reality construction, marital relationship, marital conflicts, decision-making, gender role attitudes, double standard